Tsunami - Analysis of a Hazard From Physical Interpretation to Human Impact - Lopez, Gloria I. (IntechOpen, 2012)
This book, the third in the InTech Tsunami series, has been published in order to deepen efforts towards the understanding of tsunami dynamics that seems to be never enough. As the previous books in this series, "The Tsunami Threat - Research and Technology" (January 2011) and "Tsunami - A Growing Disaster" (December 2011), this multi-disciplinary volume compiles a collection of scientific papers showing the state-of-the-art of tsunami research at different levels. The various contributions cover an array of themes that span from geological evidence to post-trauma human care, encompassing pre-tsunami analyses and modeling to post-tsunami management and preparedness techniques. As its counterparts, "Tsunami - Analysis of a Hazard: from physical interpretation to human impact" continues to present evidence and case studies from different regions of the World: from the isolated Hawaiian Islands and Northern Indian Ocean, to the edges of the Atlantic and Eastern Mediterranean.